Pemahaman tentang Budaya Supporter Sepakbola (Kajian Fenomenologi Berdasarkan Kasus Supporter Sepakbola Aremania Malang) - Harun Ahmad; Yahmun Yahmun (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2017)
The research was motivated by the debate over cultural affairs of football supporters in both theoretical and empirical levels. From these debates there are a number of relevant problems to be studied further, especially emic perspective, ie with respect to (1) the concept of football supporters socially constructed and is rooted in the view Aremania, (2) typology of football supporters among Aremania accordance with the concepts and categories as well as the basic values of what used as the basis of concepts and categorization, (3) football supporter culture is used as the common reference Aremania and the factors that inﬂuence it. This research is a qualitative phenomenological, with three methodological implications, namely (1) to put the focus on the observation and study of the social practices that take place as rergularitas daily, (2) to notice cultural aspects or dimensions that surround the practice of social actors, and (3) to put the actors as knowledgeable agents of social practice, it is necessary for the analysis of strategic conduct. The experiment was conducted in Malang, East Java, precisely in the city of Malang, with feld activities for one year, ie since the beginning of October 2011 to October 2012, and obtained the following results. First, Aremania football fans everywhere characterized as football fans in general. This is consistent with the conception of football supporters who claim that football fans are different from other fans because of the audience but also have high levels of bigotry against high club. However, it is wrong to equate Aremania with other football fans. Because, unlike fanatical fanaticism of Aremania of the other football fans. But the ethics are culture fanatic fans who wanted to be constructed by Aremania. Fanatical but should not be to the extent of harm to others. There is respect for the values of humanity while keeping the honor and dignity of the people of Malang. Secondly, based on the emic perspective, football fans have covered broader meaning than merely watching football. Devoting time and energy maximize resources belonging to supporting his favorite club is also interpreted as a football supporter culture. Even time consuming as well as the soul-body to support his/her favorite team is also defned as the culture of football fans. Third, even football and it’s important for Arema people of Malang, but its primacy over the instrumental is more pride and underwriters including a source of honor and dignity of Malang people. This is consistent with the ethos of the culture of the Malang who “comes frst” matter of honor and dignity.